Adjoint Topology Optimization Theory for Nano-Optics - Deng, Yongbo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book focuses on the topology optimization method for nano-optics. Both principles and implementing practice have been addressed, with more weight placed on applications. This is achieved by providing an in-depth study on the major topic of topology optimization of dielectric and metal structures for nano-optics with extension to the surface structures for electromagnetics. The comprehensive and systematic treatment of practical issues in topology optimization for nano-optics is one of the major features of the book, which is particularly suited for readers who are interested to learn practical solutions in topology optimization. The book can benefit researchers, engineers, and graduate students in the fields of structural optimization, nano-optics, wave optics, electromagnetics, etc.
Introduction -- Self-consistent adjoint analysis -- Dielectric material based topology optimization for wave optics -- Metal material based topology optimization for waves optics -- Topology optimization on two dimensional manifolds for wave optics. .
Keywords: Electronics; Optoelectronic devices; Nanophotonics; Plasmonics; Electronics and Microelectronics, Instrumentation; Optoelectronic Devices; Nanophotonics and Plasmonics; Mathematical optimization; Nanostructured materials -- Optical properties; Topology